GCLiPP: global crosslinking and protein purification method for constructing high-resolution occupancy maps for RNA binding proteins - Wandi S. Zhu; Adam J. Litterman; Harshaan S. Sekhon; Robin Kageyama; Maya M. Arce; Kimberly E. Taylor; Wenxue Zhao; Lindsey A. Criswell; Noah Zaitlen; David J. Erle; K. Mark Ansel (Genome Biology, 2023)
Abstract GCLiPP is a global RNA interactome capture method that detects RNA-binding protein (RBP) occupancy transcriptome-wide. GCLiPP maps RBP-occupied sites at a higher resolution than phase separation-based techniques. GCLiPP sequence tags correspond with known RBP binding sites and are enriched for sites detected by RBP-specific crosslinking immunoprecipitation (CLIP) for abundant cytosolic RBPs. Comparison of human Jurkat T cells and mouse primary T cells uncovers shared peaks of GCLiPP signal across homologous regions of human and mouse 3′ UTRs, including a conserved mRNA-destabilizing cis-regulatory element. GCLiPP signal overlapping with immune-related SNPs uncovers stabilizing cis-regulatory regions in CD5, STAT6, and IKZF1.